2017
DOI: 10.1159/000485821
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Accelerates Aggressiveness of Hepatocellular Carcinoma Cells Involving Oxidative Stress, Epithelial-Mesenchymal Transition and Non-Canonical Hedgehog Signaling

Abstract: Background/Aims: Hypoxic microenvironment, a common feature of hepatocellular carcinoma (HCC), can induce HIF-1α expression and promote the epithelial-mesenchymal transition (EMT) and invasion of cancer cells. However, the underlying molecular mechanisms have not fully elucidated. Methods: HCC cells were cultured under controlled hypoxia conditions or normoxic conditions. Transwell assays were used to examine the migration and invasion capacity. HIF-1α siRNA, cyclopamine (a SMO antagonist) and GLI1 siRNA were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 44 publications
4
56
0
Order By: Relevance
“…In summary, HCC tissue sections were incubated with GPR39 (1:300, Abcam, USA) overnight at 4°C and then flushed with PBS and re‐incubated with biotinylated secondary antibodies (Goldenbridge, Zhongshan, China) according to the SP‐IHC assay instructions. The experiment was performed according to our previously reported protocol …”
Section: Methodsmentioning
confidence: 99%
“…In summary, HCC tissue sections were incubated with GPR39 (1:300, Abcam, USA) overnight at 4°C and then flushed with PBS and re‐incubated with biotinylated secondary antibodies (Goldenbridge, Zhongshan, China) according to the SP‐IHC assay instructions. The experiment was performed according to our previously reported protocol …”
Section: Methodsmentioning
confidence: 99%
“…In hepatocellular carcinoma (HCC) patients, SMO mutation at the C-terminal lysine (K575M) involves the binding between PTCH and SMO to alleviate SMO from PTCH suppression to activate the downstream signaling [57]. Liu et al found that hypoxia-inducing oxidative stress, epithelial-mesenchymal transition (EMT), and activation of the non-canonical SHH signaling pathway aggravates the invasiveness of HCC cells [58]. Chen et al found that the SHH pathway induces the migration and the invasion of HCC cells via activation of focal adhesion kinase (FAK)/P13K/AKT signaling-mediated matrix metalloproteinase-2, as well as matrix metalloproteinase-9 production [59].…”
Section: Shh In Liver Injury and Hepatocarcinogenesismentioning
confidence: 99%
“…For example, the paradoxical trend towards increase in glycogen content after IH, despite inhibition of AKT/GSK-3β, may implicate hypoxia inducible factor (HIF)-mediated induction of glycogen synthase 1 [33]. Third, in addition to JNK, changes in other stress/hypoxia-inducible pathways including Sestrins, oxidative stress, as well as microRNA profiles should be considered in interpreting the metabolic consequences of IH in liver cells [34][35][36].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%